ENDOPHYTIC TESTING OF Serratia marcescens strain NPKC3_2_21 AGAINST INPARA 3 RICE VARIETY - Gunawan Sutio; Iskandar Iskandar; Lilik Tri Indriyati; Gunawan Djajakirana (BIOVALENTIA: Biological Research Journal, 2023)
Pest management is a crucial concern, especially when dealing with insect pests that can cause extensive damage to agricultural crops and the economy. One such pest is the rice stem borer (Scirpophaga innotata), which infests rice stems and poses a significant threat. To combat these pests, various microbial agents have been developed for effective pest control. Among these, the endophytic microbe in biological plant protection plays a key role in the program of sustainable pest management. An endophytic bacterium, Serratia marcescens strain NPKC3_2_21, has been identified as a key player in sustainable pest management, particularly in rice crops. In this study, we aimed to investigate the endophytic characteristics of S. marcescens strain NPKC3_2_21 in the swamp rice plant of the Inpara 3 variety of swamp rice plants. To establish its roles. Marcescens as an endophytic bacterium in rice plants, specifically the Inpara 3 variety, we conducted tests by inoculating bacteria on the plant tissue of rice plants that have been sterilized rice plant tissues with the bacteria. We assessed the presence of S. marcescens strain NPKC3_2_21 in plant tissues by applying isolates to the surface of rock wool, which supported the growth of wet rice plants aged ten or over ten days or older after planting. Samples were collected from the underside of the stem, the bottom of the leaves, and the roots on days 2, 7, and 14 after the application of isolates to the rock wool. The samples were then washed in 70% alcohol and 4% chlorox for 30 seconds and subsequently isolated on Luria Bertani (LB) agar media. Furthermore, we conducted tests to determine the ligninolytic, cellulolytic, and proteolytic activities of S. marcescens, which helped elucidate its endophytic ability. Based on the result, the endophytic capabilities. Based on the results, we found that S. marcescens strain NPKC3_2_21 exhibited endophytic characteristics solely in the stem tissue of the Inpara 3 rice variety. However, we did not observe its presence in the root and leaf tissues.